Ripening Trends of Vitis vinifera L. cv Sugrasixteen (SABLE SEEDLESS®) Table Grapes at Different Crop Loads and Bunch Sizes - Viljoen, N.; Nieuwoudt, H.H.; Young, P.; Viljoen, D.W.; Kidd, M.; Avenant, J. H.; Avenant, Eunice (South African Journal of Enology and Viticulture, 2024)
Crop load and bunch size manipulation are two prominent viticultural practices used in the production of Vitis vinifera L. cv. Sugrasixteen table grapes. However, their respective effects on berry ripening are unknown and were investigated in this study. A split-plot vineyard block design with three different crop loads (low, medium, and high) as the main treatments and two bunch size treatments (small and large) as the subplot factors were used. Weekly berry samples from veraison to harvest from each treatment were analysed for mass, total soluble solids (TSS), titratable acidity (TA), and pH. Data mining established the ripening trends and explored the possibility of estimating optimal harvest dates using EC50 values. Results showed that berries of large bunches had higher average mass than small bunches during ripening. Increased crop loads resulted in berries with lower mass, TSS and TSS: TA ratio, and delayed berry ripening. Conversely, berries from the low crop load increased in mass and accumulated TSS faster during ripening than higher crop loads, reaching EC50 two to four days earlier with accumulation starting to slow down at higher values. EC50 could be used to estimate harvest dates for low to medium crop loads, but not for high crop loads. This study provides the first in-depth analysis of SABLE SEEDLESS® ripening trends concerning crop load and bunch size management. The results have implications for the grape’s overall eating quality. The statistical prediction of optimal harvest dates for lower crop loads could have practical benefits for the industry.